Removal Of Arsenic Using Synthetic Iron Oxyhydroxide - Mohd Aaznan, Nur Aina Najeehah (Universiti Sains Malaysia, 2018)
Removal of arsenic from mine waste water using iron-oxide-based absorbents are getting prevalent as using the absorbents are simpler and of low cost. In this research work, selected samples of synthetic iron oxyhydroxide powder were obtained. After characterization, these sample powders were used as an absorbent in the arsenic removal experiment. The powdered samples were placed in separate 250 mL conical flask containing 100 mL of As (V) standard solution of varying concentrations (5, 7, and 9 ppm). The experiment was conducted for 8 hours with 20 mL volume of aliquot samples taken at 1, 3, 5, and 8 hours interval hour. The concentration of the As after the removal experiment in each aliquot sample was analysed using ICP-OES. The XRD pattern of the powdered samples obtained showed major characteristic peaks of goethite and hematite. Surface morphology of the powdered samples displayed dendritic features and were highly porous. These features were found to enhance the recovery of As from the standard solution prepared. The percentage of As removed at varying concentration of As was found to be in the range of 28.9% to 99.2%. The solid residues after the arsenic removal experiment were also characterised. From XRD phase analysis, the presence of arsenic oxide (As2O3) was detected. The surfaces of the solid residues were observed to be smoother and less dendritic from the SEM photomicrograph. It can be assumed that arsenic species were adsorbed into the pores on the surface of the synthetic iron oxyhydroxide powder samples after the arsenic removal experiment.